Total Synthesis of Cribrostatin 6 - Knueppel, Daniel (2009)
The total synthesis of antimicrobial and antineoplastic cribrostatin 6 was accomplished in only four steps in the longest linear sequence and five total steps from commercially available starting materials. The key step employed a tandem 4-π electrocyclic ring opening, radical cyclization, and homolytic aromatic substitution sequence to afford the tricylic core of the natural product, which was converted to cribrostatin 6 via a subsequent, one-pot oxidation.